(untitled) (Texas Journal of Engineering and Technology, 2023)
The qualitative parameters of the provision of services are evaluated on the basis of subjective parameters that depend on the consumer properties of passengers, and objective parameters that depend on existing service standards, as well as quantitative values based on retrospective data.